Literature on Adam and Eve : collected essays - Anderson, Gary A., 1955-; Stone, Michael E., 1938-; Tromp, Johannes (Leiden ; Boston : Brill, 2000)
For many centuries, the acts and destinies of the first-created human beings, Adam and Eve, have intrigued artists, story-tellers and theologians alike. This volume is a collection of articles on these traditions, written by some of the foremost scholars in the field. The volume consists of two parts. In the first part G.A. Anderson and M.E. Stone have combined a number of studies on the rich variety of Adam and Eve-traditions, from the Life of Adam and Eve onwards to late medieval writings in Armenian. The second part, edited by Johannes Tromp, consists of papers read at the 1998 Leiden symposium, and deals more specifically with the Life of Adam and Eve.
The penitence narrative in the Life of Adam and Eve / Gary A. Anderson -- The fall of Satan and Adam's penance: three notes on The books of Adam and Eve / Michael E. Stone -- The punishment of Adam and Eve in the Life of Adam and Eve ; The exaltation of Adam and the fall of Satan / Gary A. Anderson -- The angelic prediction in the primary Adam books / Michael E. Stone / Ezekiel 28, the fall of Satan, and the Adam books / Gary A. Anderson / The legend of the cheirograph of Adam ; Selections from On the creation of the world by Yovhannēs T'lkuranci'i : translation and commentary / Michael E. Stone -- The original form of the Life of Adam and Eve : a proposal / Gary A. Anderson -- The literary development of the Life of Adam and Eve / Marinus de Jonge -- The exoneration and denigration of Eve in the Greek Life of Adam and Eve / John R. Levinson -- Cain and Abel in the Greek and Armenian/Georgian recensions of the Life of Adam and Eve / Johannes Tromp -- Sünde, Busse und Gnade in dem Leben Adam und Evas / Martin Meiser -- Adam als Bauer, oder, Die Ätiologie des Ackerbaus in Vita adae 1-21 und die Redaktionsgeschichte der Adamviten / Jan Dochhorn -- The Christian origin of the Greek Life of Adam and Eve / Marinus de Jonge.
Includes bibliographical references (pages 365-374) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Life of Adam and Eve -- Criticism, interpretation, etc; Vie d'Adam et Ève -- Critique, interprétation, etc; Life of Adam and Eve; Adam und Eva; RELIGION -- Biblical Studies; Aufsatzsammlung; Leven van Adam en Eva (apocrief); Criticism, interpretation, etc